Physical and mechanical properties of raspberries subjected to osmotic dehydration and further dehydration by air- and freeze-drying - Sette, Paula Andrea (2016)
The aim of this study was to analyze the effect of the application of dry and wet sucrose infusions, as pretreatments previous to air- and freeze-drying, on mechanical and physical properties of raspberries: water sorption, glass transition temperature (Tg), molecular mobility, texture and rehydration properties. Different dry and wet sugar infusions were prepared using combinations of additives: sodium bisulphite, citric acid, sodium bisulphite and citric acid, and no additives. These specific pretreatments are often used to obtain better sensorial characteristics of fruits upon further drying. After the dehydration step (air- or freeze-drying), all the samples were in the supercooled state. Pretreated samples presented lower Tg values and lower spin–spin relaxation times than control samples. Regarding texture, pretreated samples showed lower firmness than control samples. Also, freeze-dried pretreated samples showed higher firmness and lower deformability than air-dried pretreated ones. When considering the hygroscopicity, freeze-dried samples were more hygroscopic than air-dried ones. The fresh-like dried raspberries obtained could be directly consumed as snacks or incorporated in a composite food, such as a cereal mix. In this latter case, pretreated fruits would be more suitable, since their rehydration capacity at short times was relatively low.